When art, science and politics are found: a reflection on the experience of “Vila dos poetas”, as a Freirean práxis (Research, Society and Development, 2020)
The objective of this study was to report the experience in the light of Paulo Freire about an experience carried out in a village of residents of the municipality of Maracanaú-Ceará. It is a qualitative study of the experience report type. The experience was carried out from the discipline of popular education and school from the perspective of health promotion of the Postgraduate Program in Collective Health at the State University of Ceará. The visit took place in the second half of 2018, and residents were interviewed in order to understand the vision and perspective of popular education and health carried out in the environment in which they lived. Dialogic conversations were carried out using the conversation wheel strategy to record information. It can be seen that the lifestyle of the residents is shared in a way that enables the interaction (action) of everyone who lives in the environment in daily and financial activities. It is concluded that the non-formal environment as a teaching practice enables knowledge and knowledge in a shared way and maturation of the human being as a social being.